THE EFFECT OF LEADER MEMBER EXCHANGE (LMX) AND TEAM MEMBER EXCHANGE (TMX) ON EMPLOYEE PERFORMANCE THROUGH AFFECTIVE COMMITMENT AT PT PERKEBUNAN NUSANTARA X - Andika Dhyta Vernanda (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research aims to determine the effect of Leader Member Exchange (LMX) and Team Member Exchange (TMX) on employee performance through Affective Commitment. The population in this study were all employees of PT Perkebunan Nusantara X. The analytical tool used was Path Analysis by collecting basic data through questionnaires. From the results of the analysis, it can be concluded that LMX and TMX has a significant effect on positive affective commitment, while LMX has no significant positive effect on employee performance, TMX has a significant effect on employee performance, and affective commitment has a significant effect on employee performance. Therefore, affective commitment is a good intervening variable, especially on the effect of LMX and TMX toward employee performance. Keywords: Leader Member Exchange, Team Member Exchange, Human Resources Management